Revenue Administration : Taxpayer Audit--Use of Indirect Methods. (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note examines the use of indirect methods in a taxpayer audit. Indirect methods involve the determination of tax liabilities through an analysis of a taxpayer's financial affairs utilizing information from a range of sources beyond the taxpayer's declaration and formal books and records. Assessments are often based on circumstantial evidence indicating a reasonable estimate of the taxpayer's correct liability. This note describes why tax administrations need to use indirect audit methods. Indirect audit methods commonly used by tax administrations are elaborated. The legislative requirements for the use of indirect audit methods are also analyzed.